Suppressing small-scale self-focusing of high-power femtosecond pulses - Mikhail Martyanov; Vladislav Ginzburg; Alexey Balakin; Sergey Skobelev; Dmitry Silin; Anton Kochetkov; Ivan Yakovlev; Alexey Kuzmin; Sergey Mironov; Ilya Shaikin; Sergey Stukachev; Andrey Shaykin; et al. (High Power Laser Science and Engineering, 2023)
It was shown experimentally that for a 65-fs 17-J pulse, the effect of filamentation instability, also known as small-scale self-focusing, is much weaker than that predicted by stationary and nonstationary theoretical models for high B-integral values. Although this discrepancy has been left unexplained at the moment, in practice no signs of filamentation may allow a breakthrough in nonlinear pulse post-compression at high laser energy.